2018
DOI: 10.3329/jbau.v16i2.37984
|View full text |Cite
|
Sign up to set email alerts
|

Historical trends and variability of temperature extremes in two climate vulnerable regions of Bangladesh

Abstract: Research on temperature extremes deserves more importance because it reacts sensitively to climate change. As elsewhere across the world, Bangladesh has already become a victim of temperature extremes. Hence, this study was conducted to assess the trends and variability of 11 temperature-related extreme indices based on daily maximum (TX) and daily minimum (TN) temperature recorded at Rajshahi and Barisal over the period 1976–2015. The indices were calculated on annual basis and their average annual and decada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In Bangladesh, many studies were performed to investigate the spatiotemporal variations of extreme climate indices (Hasan et al, 2013;Shahid et al, 2016;Mahmud et al, 2018). These studies reported that warm temperature events (cold temperature events) are rising (decreasing).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh, many studies were performed to investigate the spatiotemporal variations of extreme climate indices (Hasan et al, 2013;Shahid et al, 2016;Mahmud et al, 2018). These studies reported that warm temperature events (cold temperature events) are rising (decreasing).…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported that warm temperature events (cold temperature events) are rising (decreasing). However, the studies mentioned above are either concentrated on the two regions, and a limited number of meteorological stations (Mahmud et al 2018), short time scales and a limited number of temperature indices (Khan et al, 2019), different data sources (Hasan et al, 2013). Besides, it is unclear whether and how those indices affect temperature extremes in Bangladesh both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%